Development of a PID Controller by Tuning Fuzzy Applied to a Rotational System (Inverted Pendulum) (2015)
The inverted pendulum system has arised a great interest in the control and academia areas, this system modeling presents many difficulties associated with the control problems in the real world. This paper presents a different way to develop a control strategy for the system in question, based on the design and implementation of the rotational pendulum system, then employing the same modeling strategies by using the system identification methods, based on the artificial intelligence neural networks (N-FIR), to finally taking the tuning fuzzy control step, for the different physical conditions caused on the pendulum (change in length and/or mass), which are validated, with good results on the real system developed.